تحليل الحساسية للقيمة الحالية الضبابية لمشاريع السكك الحديدية - الشيخ, دانا مروان (Latakia University Journal -Engineering Sciences Series, 2018)
There are significant uncertainties associated with the optioneering stage at the economic evaluation of major projects, and as a result, methods have been developed to help informing the preferred option. To address the limitations inherent in traditional methods this paper proposes a new mathematical model, based on Fuzzy Sets Theory. This model suggests transforming project cost expenditures and returns into triangular fuzzy numbers, to be then used in estimating the project economic criteria, namely fuzzy present worth. And then apply a parametric study to undertake fuzzy sensitivity analyses, which can be used as a support tool to select the preferred investment option. The developed method serves as a tool for use in the arena of decision-making. The applicability of the proposed model is demonstrated by a case study that isStudy for the Improvement of Aleppo&Damascus railway line. تحليل الحساسية للقيمة الحالية الضبابية لمشاريع السكك الحديدية هناك درجة عدم تأكد كبيرة مرتبطة بالبدائل المدروسة في الجدوى الاقتصادية لمشاريع البنى التحتية الضخمة، ونتيجة لذلك تَّم تطوير العديد من الطرق للمساعدة على تحديد البديل الأفضل. لمعالجة التقصيرات الكامنة في الطرق التقليدية يقترح هذا البحث نموذجاً رياضياً جديداً، يستند على نظرية المجموعات الضبابية حيث يعتمد هذا النموذج على تحويل كلف وعائدات المشاريع الهندسية إلى أرقام ضبابية مثلثية ليتم استخدامها في تقدير معايير المشروع الاقتصادية، تحديداً قيمة المشروع الحالية الضبابية، ومن ثم تطبيق دراسة بارامترية للقيام بتحليل الحساسية الضبابي. حيث سيتم استخدام الدراسة البارامترية كأداة لدعم اتخاذ القرار لتحديد بديل الاستثمار الأفضل. تخدم الطريقة المقترحة كأداة سهلة الاستخدام في مجال اتخاذ القرار. هذا وقد تمَّ توضيح تطبيق النموذج المقترح من خلال دراسة حالة وهي دراسة تطوير وتحديث لخط السكة الحديدية لحلب ودمشق.